Policy formulation and actor roles in the expanded Kenyan free maternity policy (Linda Mama): A policy analysis. - Boniface Oyugi; Zilper Audi-Poquillon; Sally Kendall; Stephen Peckham; Edwine Barasa (PLOS Global Public Health)
In 2013, Kenya implemented free maternity services, later expanded in 2016 into the 'Linda Mama' policy to provide essential health services for pregnant women. This study explored the policy formulation background, processes, content, and actors' roles in formulation and implementation. Using a convergent parallel mixed-methods case study design, we reviewed documents and conducted in-depth interviews with national stakeholders, county officials, and healthcare workers. We applied a theoretical framework capturing the background and context, processes, content, and actors. The study spanned national, county, and facility levels within Kenya's health system. Data were audio-recorded, transcribed, and analyzed using a framework thematic approach. Findings showed that political imperatives and global and national goals shaped the expanded policy, drawing on previous learnings. Actor power played a crucial role in shaping policy direction, reflecting their interests and capacity to influence decisions. The policy aimed to improve coverage and administrative efficiency, with NHIF becoming the primary purchaser of services to ensure sustainability and address legal challenges. The policy design, marked by conflicts and time pressures, required a collaborative approach to reconcile design and costing differences. Despite differing interests, discussions and dialogues were essential for leadership and conflict management, culminating in key policy documents. A committee was established for stakeholders to freely discuss and debate the policy design, enabling relevant players to devise solutions and fostering joint commitment for implementation. Government officials, development partners, and representatives significantly influenced policy formulation. Beneficiary representatives had limited awareness of public participation opportunities. National and county actors supported achieving audit, research, financing, and strategic operational goals crucial for policy implementation. In conclusion, this study highlights the continued significance of policy analysis frameworks and theories in understanding the complex nature of policy development. These findings offer valuable insights for countries designing or redesigning healthcare policies and provide relevant information to academic communities.